Sistokel: Laporan Kasus - Shariff, Fonda Octarianingsih; Septia Rini, Vica Sukma (Medula, 2025)
Anterior wall prolapse (cystocele) occurs when the front wall of the vagina bulges. The patient is 52 years old with complaints of pain and soreness in the vaginal canal area for the past 6 months which has worsened for the last 3 weeks. Complaints are accompanied by a small amount of urination, and if the patient coughs or sneezes it is always accompanied by a small amount of urine output. The patient also complained of lower abdominal pain that radiated to the waist about 6 months ago, the pain came and went, and the pain got worse when the patient was active, especially when urinating, and decreased when the patient rested. The patient has no history of diabetes mellitus but has a history of hypertension. First menstruation at the age of 11 years. The patient did not use contraception. Based on the diagnosis based on anamnesis, physical examination, gynecological examination and supporting examinations, there is Cystocele. In the anamnesis, there were complaints of pain and soreness in the vaginal canal area since 6 months ago and worsened in the last 3 weeks. Complaints are accompanied by a small amount of BAK, and if the patient coughs or sneezes it is always accompanied by a small amount of urine output. The patient has a history of hypertension and is taking Amlodipine 5mg. History of menarche: 11 years, regular menstrual cycle, length of menstruation: 3-4 days with history of P3A0 pregnancy. On physical examination, external obstetric and gynecological examination revealed tenderness in the hypogastric region. On internal examination with VT there was no palpable protrusion, then the patient was asked to perform the Valsalva maneuver and an organ protrusion appeared from the vagina. On a supporting ultrasound examination, the results of the uterus were within normal limits. The patient goes home and is given education not to lift heavy loads and strain.